Synthesis of Resolvin D6 and the Silyl Ether of the Resolvin E2 Methyl Ester via trans-Enynyl Alcohols - Morita, Masao; Tanabe, Shuhei; Arai, Tomoya; Kobayashi, Yuichi (Synlett, 2019)
Two trans-enynyl alcohol intermediates corresponding to the C1–C8 and C13–C22 parts of resolvin D6 (RvD6) were prepared through the Hudrlik–Peterson reaction of the TMS-substituted trans-epoxy alcohols with TMS-acetylide and subsequent TMS-desilylation. These intermediates were coupled with a 1,4-dihalo-2-butyne derivative under copper catalysis, and the resulting acetylene was reduced with Zn(Cu/Ag) to afford the TBS ether of RvD6 methyl ester. Desilylation with TBAF yielded the γ-lactone of RvD6, which was hydrolyzed to RvD6. The total yield of RvD6 was 1.9% in 19 steps from (3-trimethylsilyl)propargyl alcohol. The TBS ether of RvE2 methyl ester was also synthesized.
Keywords: resolvin D6; resolvin E2; stereoselective synthesis; epoxide ring opening; semi-hydrogenation; zinc; enynes